The survival of the city living and thriving in an age of isolation - Glaeser, Edward L. (New York Penguin Press, 2021)
From New York to New Delhi, COVID-19 has had a devastating impact on our urban world - how can we adjust to this new reality and what lessons can we learn from the past? In this urgently relevant book, leading experts Edward Glaeser and David Cutler examine the history and future of the global city. They argue the biggest threats are those we have created ourselves - inequalities in housing, health, work and education - and that we need to address these as a matter of urgency if our cities are to continue to thrive and drive economic growth and prosperity. They conclude by proposing some practical measures that governments and citizens need to act on to ensure the survival of the city around the world.
Keywords: City and town life--United States